FAKTOR-FAKTOR YANG MENYEBABKAN MUNCULNYA CALON PERSEORANGAN PADA PEMILIHAN BUPATI DAN WAKIL BUPATI GARUT TAHUN 2013 - Hermanto, Rudi; Sulaeman, Affan; Kartini, Dede Sri (Al-Ijtima`i: International Journal of Government and Social Science, 2018)
This paper examines the factors that led to the emergence of independent candidates for Election of Regent and Vice Regent of Garut in 2013. The number of candidates who register through independent channels reached 22 candidate pairs with diverse professional and organizational background, after verified 4 pairs of candidates contesting with 46 candidate pairs from political parties / coalitions of political parties. This independent candidate is present amid the political dynamics of Garut, which is always colored by political elite conflict and unusual change of regent due to corruption case and violation of ethics / legislation. By using qualitative approach with interview technique this paper discusses 3 factors that cause the emergence of individual candidate, that is First,Â  institutional factor of weak party party, Second, Factor of recruitment process of exclusive and centralized political party. Third is the circulation factor of local political elites, where individual candidates arise as the new middle class increases, dissatisfaction with public service and civil service, and the barrage of elite political conflicts that occur prior to the election of Garut Regent and Vice Regent of 2013.